The Influence of Club Image, Sponsorship, and Fan Loyalty on Football Merchandise Purchase Intention - Andri Agape Banjar Nahor; Muslimin Muslimin (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
This study examines the influence of club image, sponsor factors, and fan loyalty on the purchase intention of official merchandise among Bali United supporters. The focus of the research is to understand how these three factors contribute to driving merchandise sales in sports marketing, with the aim of providing insights that can improve the club's revenue strategies. By adopting a quantitative approach, primary data were collected from 87 respondents who are active supporters of Bali United, using an online questionnaire. The data were analyzed using multiple linear regression to evaluate the significance and direction of the relationships between the variables. The results reveal that each of the factors, sponsor factors and fan loyalty has a positive and significant effect, meanwhile club image has no significant effect on the intention to purchase official merchandise. This indicates that a stronger perception of the relevant and reputable sponsorships, and higher levels of fan commitment all contribute to an increased likelihood of supporters purchasing merchandise. The findings highlight the synergistic role of branding, partnerships, and community engagement in influencing consumer behavior within the sports fandom context. A positive impact from sponsor factors, such as the alignment of brands with the club's values, enhance the overall appeal of the merchandise. Moreover, fan loyalty acts as a significant driver, as loyal fans are more likely to invest in merchandise as a way to support their club. This study concludes that while Bali United’s club image does not significantly influence fans’ intention to buy merchandise, sponsor factors and fan loyalty have a positive and significant effect on purchase intention; therefore, strengthening fan loyalty and effectively managing sponsorship partnerships are key drivers in maximizing merchandise sales potential, while club image plays an indirect role.